2022
DOI: 10.3168/jdsc.2022-0222
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of activity of antioxidant enzymes, lysozyme content, and protein degradation in milk contaminated with heavy metals (cadmium and lead)

Abstract: The aim of this study was to evaluate the effect of added Cd and Pb to milk on its stability by determining antioxidant enzymatic activities, lysozyme content, and protein degradation. Antioxidant enzymatic activities were spectrophotometrically determined by superoxide dismutase, catalase, xanthine oxidase, and glutathione peroxidase assays; lysozyme was identified and quantified by HPLC-UV analysis, and protein degradation was investigated by spectrophotometric analysis of advanced oxidation protein products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Protein degradation, occurring indiscriminately, can reduce the quality of milk. However, due to the quantity ingested, it would hardly have repercussions that could be perceived in the short term (Grassi et al, 2022; Lorençoni et al, 2021; Ribeiro et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Protein degradation, occurring indiscriminately, can reduce the quality of milk. However, due to the quantity ingested, it would hardly have repercussions that could be perceived in the short term (Grassi et al, 2022; Lorençoni et al, 2021; Ribeiro et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In contaminated environments, lead (Pb) and cadmium (Cd) are two heavy metals that are frequently found together. Both forms of heavy metals are commonly found in water habitats polluted by lead paint, car emissions, industrial pollution, and mine extraction byproducts (37). Ecotoxicological studies showed that Alburnus mossulensis fish that collect Cd in their bodies had hepatotoxic consequences, such as a decrease in total antioxidant capacity and an increase in oxidative damage to lipids and proteins (38).…”
Section: Assessment Of Health Risksmentioning
confidence: 99%